Fungsi Worldview Islam dalam Kehidupan Seorang Muslim - Sumiran, Sumiran; Anshori, Nanang; Hidayah, Nur (Lembaga Yasin AlSys, 2025)
The Islamic worldview (worldview Islam) serves as a foundational framework shaping the perspective, life orientation, and behavior of a Muslim in all aspects of existence. A deep understanding and application of the Islamic worldview are essential to ensure that every dimension of spiritual, social, economic, and political life aligns with principles derived from the Qur’an and Sunnah. This article aims to elaborate on the fundamental functions of the Islamic worldview in character formation, behavioral guidance, and the direction of a Muslim’s life purpose. Utilizing a library research method, the study finds that the Islamic worldview plays a critical role in establishing firm ʿaqīdah (creed), guiding a holistic way of thinking, and serving as a reference for decision-making grounded in Divine values. Moreover, the Islamic worldview provides a strong moral foundation for confronting the challenges of modernity and globalization. Therefore, the proper internalization of the Islamic worldview functions as both an ideological and spiritual basis for realizing a meaningful life that earns the pleasure of Allah SWT.